Characterization of enterocins produced by Enterococcus mundtii isolated from humans feces - Alessandra Einsfeld Ferreira; Natália Canal; Daiana Morales; Daiane Bopp Fuentefria; Gertrudes Corção (Brazilian Archives of Biology and Technology, 2007)
The aim of this study was to characterize bacteriocins produced by 70 strains of Enterococcus mundtii.Four strains exhibited antibiotic activity towards Listeria innocua, L. monocytogenes, Lactobacillus plantarum, and Salmonella Enteritidis. They remained active under temperatures of up to 121ºC for 20 min, and under pH treatments that varied from 2.0 to 10.0. Antimicrobial activity was maintained during the storage test for 60 days under freezing. The kinetics of production revealed the peak activity of 1600 AU /mL during the logarithmic growth phase and the molecular weight found was approximately 3.0 kDa. The characterization of the products with antimicrobial activity indicated their proteic nature, presenting a typical kinetics of primary metabolite and a molecular weight similar to many purified enterocins. O objetivo do presente estudo foi caracterizar bacteriocinas produzidas por 70 cepas de Enterococcus mundtii. Estas foram caracterizadas quanto a sua atividade antimicrobiana, sensibilidade ao aquecimento, pH, armazenamento e enzimas proteolíticas. Foi também determinada sua cinética de produção e peso molecular. Entre as 70 cepas analisadas, quatro apresentaram atividade antibiótica contra Listeria innocua, L. monocytogenes, Lactobacillus plantarum, e Salmonella Enteritidis. Esta atividade foi mantida em temperaturas até 121ºC por 20 minutos, e sob condições de pH entre 2,0 e 10,0. A atividade antimicrobiana foi mantida nos testes de armazenamento a -20°C, por 60 dias. A cinética de produção revelou picos de atividade de 1600 AU/mL durante a fase logarítmica de crescimento e o peso molecular foi de aproximadamente 3,0 kDa. A caracterização dos produtos com atividade antimicrobiana revelaram suas naturezas protéicas, cinéticas de metabólito primário e peso molecular semelhante aos das enterocinas já purificadas.